Production and Characterization of Aluminum Reinforced with SiC Nanoparticles - Francisca Rocha; Sónia Simões (Metals, 2023)
Aluminum matrix nanocomposites have been the subject of much attention due to their extraordinary mechanical properties and thermal stability. This research focuses on producing and characterizing an aluminum matrix reinforced with silicon carbide (SiC) nanometric particles. The conventional powder metallurgy route was used to produce the nanocomposites, and the dispersion and mixing process was carried out by ultrasonication. The conditions of the dispersion and the volume fraction of the SiC were evaluated in the production of the nanocomposites. Microstructural characterization was carried out using optical microscopy (OM), scanning electron microscopy (SEM), energy dispersive X-ray spectroscopy (EDS), and electron backscatter diffraction (EBSD). Mechanical characterization was carried out using hardness and tensile tests. The dispersion agent was investigated, and isopropanol leads to better dispersion with fewer agglomerates. Increasing the volume fraction of the reinforcement improves the hardness of the nanocomposites. However, greater agglomeration of the reinforcement is observed for larger volume fractions. The greatest increase in hardness (77% increase compared to the hardness of the Al matrix) is obtained with 1.0 vol. % of SiC, corresponding to the sample with the best dispersion. The mechanical characterization through tensile tests attests to the effect of the reinforcement on the Al matrix. The main strengthening mechanisms identified were the load transfer, the texture hardening, Orowan strengthening, and the increase in the density of dislocations in the nanocomposites.